PELATIHAN JURNAL PENYESUAIAN DAN JURNAL PEMBALIK BAGI SISWA/I SMA KRISTOFORUS I - Amin Wijoyo; Ignatius Flora De Mayo; Michelle Rich (PROSIDING SERINA, 2021)
Community service is an activity that aims to help educate students at Kristoforus High School as well as being part of our participation from Tarumanagara University as a form of community service and providing debriefing for high school students preparing for higher education. This program is to contribute in particular in developing education through basic accounting subjects about adjusting journals including adjusting entries, deferral types, accrual types, and reversing journals. The PKM implementation method is carried out online through the Zoom Meetings media. Submission of material regarding adjusting journals is done by presenting material through powerpoint which is then followed by a small game containing questions about the material provided through the kahoot website. The results of this activity for students are increase knowledge in the field of accounting in understanding adjusting journal entries and reversing entries. After gaining new knowledge and training, the students of SMA Santo Kristoforus 1 are expected to be able to prepare themselves for higher education. society, accounting, online, adjusting journal